Unions' bargaining coordination in multinational enterprises - Domenico Buccella (SERIEs - Journal of the Spanish Economic Association, 2013)
This paper investigates the patterns of bargaining in multinational enterprises (MNEs) in the presence of labor unions coordination activities. It derives the bargaining regimes which arise as sub-game perfect equilibria, and considers both simultaneous and sequential games where parties choose whether to coordinate wage negotiations across subsidiaries. It shows that unions' per member transaction costs may attenuate the conflict of interests between bargaining parties as regards the centralization level at which negotiations should take place.
Keywords: C78; F23; J51; D60; 330; Bargaining; Multinational enterprises; Labor unions